The effect of repair protocols and chewing simulation on the microtensile bond strength of two resin matrix ceramics to composite resin - Annan Ahmed Elkassaby; Mohamed M. Kandil; Ghada Atef Alian (BMC, 2024)
Abstract Background To assess the micro tensile bond strength (µTBS) of two resin matrix ceramic (RMC) blocks bonded to composite resin by using different repair protocols with and without chewing simulation (CS). Materials and methods Two resin matrix ceramic blocks (Vita Enamic and Lava Ultimate) were divided into 4 groups according to the surface treatments: Bur grinding (control), Bur grinding + silane, 9.5% HF acid etching, and 9.5% HF acid etching + silane. The single bond universal adhesive was applied on all specimens after the surface treatments according to the manufacturer's instructions, it was administered actively on the treated surface for 20 s and then light cured for 10 s, followed by incremental packing of composite resin to the treated surface. Each group was further divided into 2 subgroups (with/without chewing simulation for 500,000 cycles). A micro tensile bond strength test was performed for each group (n = 15). The effect of surface treatments on the materials was examined by using a scanning electron microscope (SEM). The micro tensile bond strength (MPa) data were analyzed with a three-way ANOVA, the independent t-test, and one-way ANOVA followed by the Tukey post-hoc test. Results µTBS results were significantly higher for Lava Ultimate than Vita Enamic for all the surface treatment protocols with (p < 0.01). The chewing simulation significantly negatively affected the micro-tensile bond strength (p < 0.001). Bur grinding + saline exhibited the highest bond strength values for Lava Ultimate, both with and without chewing simulation. For Vita Enamic, bur grinding + saline and HF acid + saline showed significantly higher bond strength values compared to other surface treatments, both with and without chewing simulation (p ≤ 0.05). Conclusion Bur grinding + silane could be recommended as a durable repair protocol for indirect resin matrix ceramics blocks with composite resin material.